A New Phenolic Compound from Stem of Cassia siamea and its Anti-Tobacco Mosaic Virus Activity - Yuan1, Lin; Huang1, Wenzhong; Gao1, Yan; Gao2, Xuemei; Hu2, Qiufen; Ma1, Yinhai (Asian Journal of Chemistry, 2014)
A new phenolic compound, 4-(3-hydroxy-4,5-dimethoxyphenyl)-4-oxobutanoic acid (1), was isolated from the stem of Cassia siamea. Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D-NMR techniques. Compound 1 was also tested for its anti-tobacco mosaic virus activity and it showed high anti-tobacco mosaic virus activity with inhibition rate of 18.6 %.